2009
DOI: 10.1038/sj.bjc.6604965
|View full text |Cite
|
Sign up to set email alerts
|

Influence of bevacizumab, sunitinib and sorafenib as single agents or in combination on the inhibitory effects of VEGF on human dendritic cell differentiation from monocytes

Abstract: Vascular endothelial growth factor (VEGF) inhibits differentiation and maturation of dendritic cells (DC), suggesting a potential immunosuppressive role for this proangiogenic factor. Bevacizumab, sorafenib and sunitinib target VEGF-mediated angiogenesis and are active against several types of cancer, but their effects on the immune system are poorly understood. In this study, VEGF and supernatants of renal carcinoma cell lines cultured under hypoxia were found to alter the differentiation of human monocytes t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
157
0
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 191 publications
(166 citation statements)
references
References 31 publications
5
157
0
3
Order By: Relevance
“…Alfaro et al showed that VEGF pathway inhibition using bevacizumab or sorafenib in vitro abrogated the differentiation of monocytes to DCs [58]. Another in vitro study used embryonic stem cells to show that the DC maturation mainly depends on VEGFR1 activation [59].…”
Section: Vegf Regulates DC Maturation and Its Functionmentioning
confidence: 99%
“…Alfaro et al showed that VEGF pathway inhibition using bevacizumab or sorafenib in vitro abrogated the differentiation of monocytes to DCs [58]. Another in vitro study used embryonic stem cells to show that the DC maturation mainly depends on VEGFR1 activation [59].…”
Section: Vegf Regulates DC Maturation and Its Functionmentioning
confidence: 99%
“…The functional activity of DCs depends, in part, on the expression of HLA-DR and co-stimulatory molecules (17). effect of VEGF but they expressed less HLA-DR and CD86, and this effect was suspended by the VEGF inhibitor (18).…”
Section: Discussionmentioning
confidence: 99%
“…The use of DC vaccine has also shown promising results in some reported cases in the literature (9). The use of DC vaccine in association with targeted drugs is controversial and was first assumed that it could be used with sunitinib alone, (14) although it could also be used with sorafenib as demonstrated by Alfaro et al (15).…”
Section: Commentsmentioning
confidence: 98%
“…Apparently, any of these drugs could be used in association with DC vaccine based on the Alfaro et al study (15).…”
mentioning
confidence: 99%